Understanding environmental incidents on construction sites in Australia: the causal factors, environmental impact and their relations - Andrić, Jelena M.; Wang, Jiayuan; Mahamadu, Abdul-Majeed; Zhong, Ruoyu (Journal of Civil Engineering and Management, 2019)
The construction sites are prone to environmental incidents. In this paper, the root causes of incidents and immediate actions taken after events are identified through qualitative analysis, while the environmental impacts, the cost of mitigation, time of incident occurrence, as well as the relationship between the causes of incidents and immediate actions and the causes and environmental impacts were quantitatively analysed. In total, 499 environment incidents occurred over an 8-year period on the construction sites in Australia was examined in this study. The results show that the most common causes of incidents were equipment and plant failure, oil spillage, and fuel spillage, while the most expensive incidents in terms of mitigation were flooding, poor weather, and process failures. Further, the most common actions taken immediately after incidents were cleaning and clearing, shut down of operation, plant and equipment and notifications. More than 50% of incidents resulted in the contamination of land and groundwater, while the majority of incidents occurred between 10:00 am and 12:00 am. We propose strategies for project managers and environmental managers to better understand potential environmental hazards.